(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to understand the financial management strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in facing modern business competition. This study uses a descriptive qualitative approach with primary data sources obtained through interviews and observations of MSMEs, as well as secondary data derived from books, journals, and other supporting documents. The data analysis technique uses the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that financial management strategies play a crucial role in maintaining the stability and sustainability of MSME businesses. Some business owners have implemented simple financial recording, cash flow management, and the use of digital technology in business management. However, the implementation of these strategies has not been optimal due to obstacles such as low financial literacy, mixing personal and business finances, and limited ability to use digital technology. This study is limited to a specific MSME scope, so the results cannot be generalized widely. The implications of this study are expected to serve as evaluation material and recommendations for MSMEs, the government, and related institutions in improving financial management capabilities and business competitiveness in the modern business era.